Analysis of Factors Affecting the Financial Performance in Energy Sector Companies - Boru Hotang, Keri (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2025)
This research aims to determine company size, managerial ownership, capital structure and dividend policy on financial performance in energy sector companies listed on the Indonesian stock exchange for the 2019-2023 period. Data collection method is by collecting annual financial reports on the IDX website. The number of samples used in this research was 55 observations. The research results show that the variable company size, dividend policy partially has an influence on financial performance, while managerial ownership and capital structure partially have no influence on financial performance.